Becoming an Intentional Church Community: Relationships, Security, and Discipleship in Sexual Identity and Faith Development. Issue 2 (August 2021) - Dean, Janet B.; Stratton, Stephen P.; Yarhouse, Mark A.
Drawing upon previous research with sexual minority Christian college students, we identify emergent themes important to ministry with sexual minorities integrating religious/spiritual and sexual identities: intrinsic religiosity, social relationships, self-acceptance, and complexity of identity integration. We propose a Trinitarian ministry model wherein the church serves as a holding environment—a discipling community intentionally designed to be relational, secure, and formational thereby creating a synergistic communal climate for identity development related to faith and sexuality.